Edukasi Digitalisasi Pelatihan dan Pemasaran Produk Dan Jasa Terhadap Pengelola Homestay, Villa, dan Objek Wisata Di Desa Taro - Ni Nyoman Nidya Trianingrum; I Wayan Kartimin; Ni Kadek Lani (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
In this era of globalization, villages should contribute to developing digitalization for the advancement of villages and making smart villages. Through thematic real-work lectures (KKNTs), the Digital Education program provides guidance and training to the managers of tourist attractions, villas and homestays regarding Digital Education in marketing places or tourist objects so that they can be accessed in social media. In addition, students also provide a digital education work shop with the theme “how to make a good content” with the community as a respondent that can be applied in the management of tourist attractions that exist in the village of Taro. The method used in the digital education program is starting from preparing places and equipment for the work shop of digital education. By bringing in sources that are experts in the field of digitalization as well as preparing some consumption for respondents. Activities included the implementation of digital marketing work shop, making promotional videos at several tourist attractions and home stays, making video promotional Taro tourist village, as well as taking some photos of Taro home stay and tourist objects.